Ketogenic diet and behavior: insights from experimental studies - Grabowska, Konstancja; Grabowski, Mateusz; Przybyła, Marta; Pondel, Natalia; Barski, Jarosław J.; Nowacka-Chmielewska, Marta; Liśkiewicz, Daniela (Frontiers in Nutrition, 2024)
As a journal page for full details. The ketogenic diet (KD) has been established as a treatment for epilepsy, but more recently it has been explored as an alternative or add-on therapy for many other diseases ranging from weight loss to neurological disorders. Animal models are widely used in studies investigating the therapeutic effects of the KD as well as underlying mechanisms. Especially in the context of neurological, psychiatric, and neurodevelopmental disorders essential endpoints are assessed by behavioral and motor tests. Here we summarized research evaluating the influence of the KD on cognition, depressive and anxiety-related behaviors, and social and nutritional behaviors of laboratory rodents. Each section contains a brief description of commonly used behavioral tests highlighting their limitations. 90 original research articles, written in English, performed on mice or rats, providing measurement of blood beta-hydroxybutyrate (BHB) levels and behavioral evaluation were selected for the review. The majority of research performed in various disease models shows that the KD positively impacts cognition. Almost an equal number of studies report a reduction or no effect of the KD on depressive-related behaviors. For anxiety-related behaviors, the majority of studies show no effect. Despite the increasing use of the KD in weight loss and its appetite-reducing properties the behavioral evaluation of appetite regulation has not been addressed in preclinical studies. This review provides an overview of the behavioral effects of nutritional ketosis addressed to a broad audience of scientists interested in the KD field but not necessarily specializing in behavioral tests.